Opportunities for the Digital Implementation of Legalization and Certification by Notaries Public - Pratama, Imam Endrik (Jurnal Ilmu Hukum Kyadiren, 2025)
The advancement of digital technology has brought significant changes to various aspects of life, including the notary sector. The digitalization of notary services has become a crucial issue, particularly concerning the legalization and certification of documents. This development raises questions about the prospects, legality, and legal challenges associated with its implementation. This study aims to analyze the legal standing and authority of notaries in digital legalization and certification, as well as to examine the validity of documents within the Indonesian legal system. The research employs a normative juridical approach, analyzing regulations, legal doctrines, and court decisions. According to the Notary Law (UUJN), legalization and certification fall under the authority of notaries. However, digitalization still presents challenges, such as document security and legal certainty. Therefore, clearer regulations are necessary to ensure that this process can be carried out securely and in compliance with the law